The Effect of Job Satisfaction, Employee Loyalty, and Work Commitment on Employee Performance at PT Sulsel Citra Indonesia (Perseroda) - Jusri Jusri; Hasnidar Hasnidar (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the simultaneous and partial effects of job satisfaction, employee loyalty, and work commitment on employee performance at PT Sulsel Citra Indonesia (Perseroda). This research adopts an associative quantitative approach. Data were collected through structured questionnaires distributed to 54 respondents drawn from a population of 114 permanent employees using simple random sampling. Multiple linear regression analysis was conducted using SPSS version 26. The finding that The F-test result (Fcount = 60.515 > Ftable = 2.196; sig. = 0.000) confirms that all three variables simultaneously exert a positive and significant effect on employee performance. Partially, job satisfaction (t = 3.485; sig. = 0.001) and work commitment (t = 11.685; sig. = 0.000) each have a positive and significant effect on employee performance, while employee loyalty (t = -3.080; sig. = 0.003) shows a negative and significant effect. The adjusted R² of 0.771 indicates that 77.1% of the variance in employee performance is explained by the three predictors. Work commitment emerged as the dominant predictor of employee performance, followed by job satisfaction. The negative effect of employee loyalty suggests that loyalty alone does not directly translate into higher performance unless it is accompanied by adequate motivation, job satisfaction, and organizational support. These findings are consistent with previous empirical studies conducted in the plantation and service sectors